Women’s Economic Roles in Small-Scale Agrifood Market Systems: Implications for Household Income and Sustainability - Rahmadani A, Sofia; Nurhapsa (Integrated and Sustainable Agriculture, 2025)
Small-scale agrifood market systems play an important role in supporting household livelihoods and local food supply, particularly in regions where traditional vegetable markets dominate. Women increasingly participate as vegetable traders within these systems, yet their economic roles are often underrepresented in agrifood sustainability analyses. This study examines women’s economic roles by analyzing income generation, cost structures, and contributions to household income within a small-scale agrifood market system. A quantitative descriptive approach was employed using a census survey of women vegetable traders operating in a traditional morning market in Bone-Bone Subdistrict, Indonesia. Data were collected through structured interviews and analyzed using cost–income analysis and household income contribution measures. The results indicate that women traders generate substantial net income, with variable costs comprising the largest share of total production costs. Women’s trading income contributes approximately 80% of total household income, indicating that women act as primary economic providers. These findings demonstrate that vegetable trading represents a viable livelihood strategy. Overall, women traders support both household economic sustainability and the stability of small-scale agrifood markets by maintaining daily market circulation and food supply continuity, contributing to more resilient local food systems.